Evolutionary Dynamics and a Refinement of the Neutral Stability Criterion - Pär Torstensson (Lund University, School of Economics and Management, Department of Economics, 2005)
We introduce two refinements of the neutral stability criterion, namely the ascending and the eroding neutrally stable strategies (NSS). These criteria take into account how well the NSS preform against all pure strategies in symmetric two-player games. We also present a dynamic model which supports the refinements.
Keywords: C73; 330; Evolutionary dynamics; Neutrally stable strategies; ascending NSS; Eroding NSS.